INFLUENCE OF CUSTOMER BEHAVIOUR AND CUSTOMER EXPERIENCE ON PURCHASE DECISION OF URBAN DISTRO - M. Fikri; Anita Silvianita (Business Journal : Jurnal Bisnis Dan Sosial, 2021)
The creative economy is one of the new economic concepts that intensify information and creativity and Human Resources (HR) as the main factor of production of the fashion sector is quite influential on the economic income of the Fashion Industry, especially local products offered by various distros easily accepted by the market Products sold in distro stores aimed at meeting the needs of young people This method uses quantitative methods in This study will look for the relationship between customer behavior, customer experience, to purchasing decisions Methods used to manage data using Microsoft Excel and then processed using SmartPLS, Respondents in this study there are 100 people who have made purchases in Urban Traffic. Keywords: Customer Behaviour, Customer Experience, Purchasing Decisions